ANALYSIS OF FACTORS THAT INFLUENCE CORPORATE SOCIAL RESPONSIBILITY WITH INSTITUTIONAL OWNERSHIP AS MODERATING VARIABLES ON MINING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) (2013-2016 PERIOD) - Perangin-angin, Albert Bastanta (Asosiasi Dosen Akuntansi Indonesia, 2018)
This study aims to analyze the effect of profitability, leverage, firm size, board size, and company age on corporate social responsibility with institutional ownership as a moderating variable in mining companies listed on the Indonesia Stock Exchange. The population and sample in this study are mining companies that publish annual reports and annual reports from 2013-2016 which amount to 32 companies. The sampling method was purposive sampling, so the number of units of analysis used amounted to 128 observation samples. The type of data in this study is secondary data obtained from the IDX website, www.idx.co.id. The data analysis method used is the method of multiple linear regression analysis and residual test. The results showed that simultaneously, profitability, leverage, company size, board size, and company age had a significant effect on corporate social responsibility. But partially only the size of the company and the age of the company have a positive and significant influence on corporate social responsibility. While profitability, leverage, and the size of the board of commissioners do not affect corporate social responsibility. Residual testing, institutional ownership variables as the moderating variable in this study cannot moderate the relationship between profitability, leverage, company size, board size, and company age on corporate social responsibility.